Use of CPR in hemorrhagic shock, a dog model. Issue 1 (July 2016) - Jeffcoach, David R.; Gallegos, Juan J.; Jesty, Sophy A.; Coan, Patricia N.; Chen, Jason; Heidel, Robert Eric; Daley, Brian J.
Abstract : INTRODUCTION: Cardiopulmonary resuscitation was designed for sudden cardiac events usually triggered by thrombotic phenomena. Despite this, it is routinely used in trauma resuscitations as per the American Heart guidelines. There is no data supporting the use of chest compressions in hemorrhagic shock. An evidence-based cardiopulmonary resuscitation (CPR) protocol has been developed for dogs. We sought to determine the effects and outcomes of chest compressions in hemorrhagic shock in a canine model. METHODS: Eighteen dogs were randomized to three treatment groups—chest compressions only after hemorrhagic shock (CPR), CPR with fluid resuscitation after hemorrhagic shock (CPR + FLU), and fluid resuscitation alone after hemorrhagic shock (FLU). Under anesthesia, dogs were hemorrhaged until pulse was lost; they were maintained pulseless for 30 minutes and then resuscitated over 20 minutes. Vital signs and laboratory values were recorded at determined intervals. Echocardiography was performed throughout the study. Upon termination of the study, kidney, liver, heart, and brain tissue histology was evaluated for end organ damage. Statistical significance was p < 0.05 with a Bonferroni correction for multiple comparisons. RESULTS: Blood loss and mean time to loss of pulse were similar between the groups. Dogs in the CPR group had significantly lower mean arterial pressure and higher pulse at all points compared to CPR + FLU and FLU ( p < 0.05). Ejection fraction was lower in the CPR group at 5 and 10 minutes compared to the other groups ( p < 0.05). Vital signs and laboratory results between CPR + FLU and FLU were equivalent. Two of six dogs in the CPR group died, while no dogs died in the CPR + FLU or FLU groups. Dogs in the CPR group were found to have more episodes of end organ damage. CONCLUSION: There was no benefit to chest compressions in the hypovolemic animals. Chest compressions in addition to fluid did not reverse signs of shock better than fluid alone. Further research is needed to define if there is a role of CPR in the trauma patient with hemorrhagic shock.